The effect of price transparency: Assessment of the German Highway Retail Gasoline Sector - Christoph Kleineberg (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2025)
Increasing competition and reducing market power are core interests of economists, regulators and the public to maximise aggregate social welfare. Low prices are achieved through intense competition in the retail gasoline market. The absence of fierce competition is referred to as market power. Market power is defined as a firm's ability to influence the market price. In this paper, I analyse the extent to which highway gasoline stations and the nearest truck stop influence each other's prices. The key question is whether proximity to a truck stop reduces the price of gasoline at highway stations. It is also an assessment of the impact of increased transparency on the German retail gasoline market along the highway system. The analysis is based on 287 German highway gasoline stations and the nearest truck stop. Additionally, two subsamples of 29 highway gasoline stations near truck stops and 29 highway gasoline stations located farther away from truck stops are examined. The results indicate that higher prices persist in the German highway gasoline retail market. Gasoline retailers expect the majority of customers to not compare prices between highway gasoline stations and the closest truck stop by using mobile devices. Despite offering complete price transparency, low transaction costs, and homogeneous products, highway gasoline stations maintain a dominant market position. This changes significantly if the truck stop is near the highway gasoline station (within 5 kilometres). If a driver has just passed a truck stop or seen a sign indicating a truck stop, the price premium at the highway gasoline station decreases significantly, from 12-14 Cents per litre to 2-3 Cents per litre. Consequently, traditional price transparency has a significant impact on competition, resulting in lower prices.
Keywords: D01; D40; L1; L41; 330; market power; gasoline market; market transparency; perfect competition; Edgeworth cycles